Establishing a warning index for evaluating the physiological stress of sanitation workers in high temperature weather. (August 2021) - Zheng, Guozhong; Fan, Zhuangzhuang; Ge, Meng; Li, Cong
Abstract: High temperature weather occurs frequently in recent years. As a heat-vulnerable group, sanitation workers suffer great physiological safety risks in high temperature weather. In this paper, a physiological warning index (PWI) is established to quantify the physiological stress of the sanitation workers. Firstly, the dynamic weights of the physiological parameters are calculated by the norm grey correlation method. Secondly, the PWI is established by the efficacy coefficient method and the warning level of the PWI is divided based on the relationships between the PWI and thermal sensation vote (TSV). Finally, the reasonability of the PWI is verified. The results show that the weights of the physiological parameters are dynamic, changing with the environments and the physiological states. The weight ranges of the mean skin temperature (MST), tympanic temperature (TT), systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR) are 0.036–0.538, 0.000–0.369, 0.000–0.362, 0.018–0.367 and 0.009–0.348. And the MST and DBP are more affected by the high temperature than the TT, SBP and HR. The warning interval of PWI is: (0, 0.25] (no warning), (0.25, 0.45] (mild warning), (0.45, 0.7] (moderate warning), and (0.7, 1.0] (severe warning). The PWI can provide simple real-time physiological warning and guarantee physiological health for sanitation workers in high temperature weather. Highlights: A physiological warning index is established to quantify the physiological stress. Norm grey correlation is used to obtain the weights of physiological parameters. Satisfactory value and limit value are adopted to establish the index. Weights of the physiological parameters change with the physiological states. Warning intervals of PWI are: [0, 0.25], (0.25, 0.45], (0.45, 0.7] and (0.7, 1.0].